2020
DOI: 10.1002/eji.201948411
|View full text |Cite
|
Sign up to set email alerts
|

Th2 cells promote eosinophil‐independent pathology in a murine model of allergic bronchopulmonary aspergillosis

Abstract: Repeated inhalation of airborne conidia derived from the fungus Aspergillus fumigatus (Af) can lead to a severe eosinophil-dominated inflammatory condition of the lung termed allergic bronchopulmonary aspergillosis (ABPA). ABPA affects about 5 million individuals worldwide and the mechanisms regulating lung pathology in ABPA are poorly understood. Here, we used a mouse model of ABPA to investigate the role of eosinophils and T cell-derived IL-4/IL-13 for induction of allergic lung inflammation. Selective delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 61 publications
2
21
0
Order By: Relevance
“…Dietschmann et al showed that in a mouse model of ABPA, T-cells released huge amounts of IL4, IL5 and IL13 upon stimulation with Aspergillus fumigatus conidia. They further demonstrated that T cell-specific IL4/IL13-deficient-knockout mice exhibited reduced peripheral and lung eosinophilia, suggesting that IL4 and IL13 signaling leads to recruitment of eosinophils to the lung and blood from the bone marrow [3].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dietschmann et al showed that in a mouse model of ABPA, T-cells released huge amounts of IL4, IL5 and IL13 upon stimulation with Aspergillus fumigatus conidia. They further demonstrated that T cell-specific IL4/IL13-deficient-knockout mice exhibited reduced peripheral and lung eosinophilia, suggesting that IL4 and IL13 signaling leads to recruitment of eosinophils to the lung and blood from the bone marrow [3].…”
Section: Discussionmentioning
confidence: 97%
“…Allergic bronchopulmonary aspergillosis (ABPA) is a hypersensitivity reaction to aspergillus species that predominantly affects cystic fibrosis and asthma patients [1]. Aspergillus colonization of the bronchial mucus leads to an activation of the innate immune system with a Th2predominant T cell response [2][3][4][5]. Clinical features of ABPA comprise frequent asthma exacerbations, productive cough, airway obstruction, fever, and finally leads to end-stage lung disease.…”
Section: Introductionmentioning
confidence: 99%
“…Other models of allergic aspergillosis have been described including one featuring repetitive intranasal instillation of live A . fumigatus conidia [ 55 ]. In that model, eosinophil-deficient mice had decreased expression of IL-17A.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, consistent with previously published data with ova and house dust mite induced allergies [31,54], the Siglec F + eosinophils could be divided into subpopulations based on relative expression levels of CD11c. Other models of allergic aspergillosis have been described including one featuring repetitive intranasal instillation of live A. fumigatus conidia [55]. In that model, eosinophil-deficient mice had decreased expression of IL-17A.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Dietschmann et al concluded that T-cell-derived IL-4/IL-13 is essential for A . fumigatus -induced lung eosinophilia and inflammation, while eosinophils seem to have immunomodulatory and not only inflammatory function [ 33 ]. Taken together, these results suggest that the increased susceptibility of CF patients to ABPA might be due to an exaggerate Th2 response and a deficient Th1 response.…”
Section: Pathogenesis Of Aspergillus Fumigatus mentioning
confidence: 99%